Student Identity in the EFL Classrooms - Basnet, Arjun (Journal of NELTA, 2023)
This paper explores various processes of identity construction of the students studying in English medium secondary schools in Nepal while learning English as a second /foreign language. The students in English medium schools actively participate in various classroom interactions, engage mutually in the learning process and share their feelings through which they make sense of themselves and construct various identities. By collecting information from interviews with eight participants, this qualitative study showcases that the EFL students construct multiple identities through the process of positioning, opportunity and transformation. Due to positioning, i.e., how the students situate themselves through their discursive practices and how they are situated by others, the students construct a number of identities namely, discourse identity, social identity, institution identity, authored identity, affinity identity and L1 identity, becoming and being as identity, learner identity and inner circle identity. Some of these identities, especially the former ones are constructed by virtue of opportunity whereas the later one is constructed due to transformation. These identities, however, were not found going parallel because the identities constructed in one field infused their identities in other fields.